LEGACY SPORTS EDUCATION, AND PHYSICAL EDUCATION IN BRAZIL MEGA SPORTS EVENTS (Fiep Bulletin - online, 2013)
The present study sought to explore expectations for educational and sporting legacies possible strategies of Physical Education to provide such legacy forward the realization of mega sporting events Olympics and Paralympics in Brazil in 2016. Megaeventos has a cultural and sporting legacy with colossal size and how all aspects that result in benefits and opportunities to the population, and character inheritance. Faced with this issue the federal government launched propositions highlighting the assertion of programs and Second Time Over Education, which would be strong allies for the physical education teachers develop aspects related to this legacy, but we understand that can not be the only strategy, limited reach because a portion of the Brazilian population. The goal, therefore this study aims to explore the expectations to ensure educational sports legacy. Thus, we consider necessary to carry out interventions in schools for physical education in order to seize the moment of growing interest of society in the mega sports events to enhance the education of students, arousing criticism about major events that reverberate throughout Brazilian society . Moreover, educating citizens who understand the values ??associated with the sport and the importance of daily practice and systematized the same for their quality of life and personal development. We understand that the development of educational sporting legacy should be appropriate for Physical Education, seeking to develop a sporting culture and education based on Olympic values ??that not only focuses on the training of professional athletes but an integral formation of students through the bias of schooling.
Keywords: Educational Legacy Sports; Physical Education; Sport Mega Events